External Adjustment and Equilibrium Exchange Rate in Brazil - Paiva, Claudio (Washington, D.C. : International Monetary Fund, 2006)
This paper investigates the factors behind the significant improvement in Brazil's external accounts and wide fluctuations of the real exchange rate since the floating of the real in 1999. Particular attention is devoted to the strong appreciation of the real from 2003-05. Econometric estimates of of behavioral equilibrium exchange rate (BEER) model for Brazil show that most of this appreciation was an equilibrium response to improved economic fundamentals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet